Factors Influencing Online Shopping Behaviour of Customers: A Case Study on Shopee - Heng, Tick Ying; Ho, Rui Sin; Pushpanathan, Herasiny A/P; Hu4, AnYuan (AIBPM Publisher, 2024)
As time goes by, the advancement of technology has brought tremendous impact to all fields. Consumers’ purchasing behaviour has changed due to the existence of e-commerce. Especially during the pandemic outbreak, consumers intend to purchase online instead of visiting stores due to lockdown restrictions and virus infection risks. According to the statistical data obtained from the Department of Statistics Malaysia Official Portal, Malaysia has recorded a 32.7% growth in E-commerce income by establishments in year 2021 compared to the year 2020. This study aims to examine the factors influencing online shopping behaviour by conducting a case study on Shopee. This study was carried out through data collection by using a survey questionnaire and secondary data analysis and collection obtained from other sources such as online related websites. There were 150 Shopee users who responded to the survey. At the end of this research, the findings aim to provide a clearer view of the factors that influence the online shopping behaviour of consumers including perceived usefulness, perceived ease of use, perceived convenience and perceived trust. The empirical findings shall also help to reveal insufficient of Shopee and ways to improve